Aplikasi Cerdas Terintegrasi dalam Mendiagnosa Penyakit ISPA Pneumonia Pada Balita Menggunakan Algoritma Neural Network Backprogation di Kabupaten Langkat - Ahmad Indra Harahap; Ryan Dhika Priyatna; Harry Pratama Figna; Nurhamimah Rambe (Universitas Islam Raden Rahmat, Malang, 2023)
Research using the backpropagation artificial neural network algorithm to diagnose ARI pneumonia in toddlers in Langkat Regency is very urgent. ISPA (Acute Respiratory Infection) and Pneumonia are two diseases that are still a health problem in Indonesia, especially for toddlers. These diseases are often difficult to diagnose accurately and on time, so that treatment is not optimal. This can have an impact on the high death rate due to this disease. By using the backpropagation artificial neural network algorithm, research can develop an intelligent application system that can help diagnose ARI pneumonia in toddlers with higher accuracy. In this study, the data used may include the patient's symptoms and health history, such as a history of fever, cough and shortness of breath. This method is expected to minimize diagnostic errors and increase the speed of providing appropriate treatment. Apart from that, this smart application can also help medical personnel in rural areas who may have limitations in diagnosing this disease.